Transactional Analysis Counseling: A Potential Game-Changer for Adolescent Behavioral Issues in Schools - Hasibuan, Ummi Kalsum; Netrawati, Netrawati; Ardi, Zadrian (Jurnal Bimbingan dan Konseling Terapan, 2024)
Adolescence is a period of transition marked by emotional fluctuations and behavioral changes, which can result in stress and cognitive disturbances. These challenges can be exacerbated by societal expectations and the surge of technological advancements. Within a school setting, these issues necessitate professional interventions, such as Transactional Analysis Counseling, which assists students in understanding their personality, communication styles, and behavioral patterns. This study used a descriptive research design and qualitative analysis to examine the practical application of Transactional Analysis Counseling in schools. The findings suggest that Transactional Analysis Counseling can enhance self-awareness and enable students to make more conscious, beneficial decisions in their academic and personal lives. However, continued research is necessary to assess the long-term benefits and challenges of this approach in varying school environments and student demographics.